Factors Present in Micro-Influencers and Their Influence on Consumer Buying Behavior in the Chiclayo Market, 2025 - Succe Larrea, Maria Teresa; Cumpa Llontop, Juan Diego Alejandro; Montes Tocto, Richard Ignacio; Saldaña Barboza, Alasteña (LACCEI, 2025)
This research aims to describe the relationship between the factors present in micro-influencers and their influence on consumer buying behavior in the Chiclayo market, 2025. A quantitative approach with an explanatory scope was employed to identify the causal influence of the micro-influencer factors on consumer purchase behavior. The study follows a non-experimental, cross-sectional design. The population consisted of 487,000 inhabitants of Chiclayo, and a probabilistic sampling method was used to survey 384 individuals. Data collection was carried out using a validated questionnaire adapted from Hu et al. [1] A total of 553 respondents completed the survey using this validated instrument. The data were analyzed using the PLS-SEM structural equation modeling approach. The results revealed that the factors of experience, entertainment value, and credibility of the micro-influencer significantly influence consumer purchase behavior. Specifically, entertainment value had the greatest impact (β = 0.3352; p < 0.001), followed by credibility (β = 0.3045; p < 0.001) and experience (β = 0.2260; p < 0.01). The proposed model demonstrated adequate validity and reliability. It is concluded that micro-influencers play a relevant role in purchase behavior, highlighting the importance of these factors in the design of digital marketing strategies.